Human Plasmacytoid Dendritic Cells Elicited Different Responses after Infection with Pathogenic and Nonpathogenic Junin Virus Strains - Negrotto, Soledad (J Virol, 2015)
The arenavirus Junin virus (JUNV) is the etiologic agent of Argentine hemorrhagic fever. We characterized the JUNV infection of human peripheral blood-derived plasmacytoid dendritic cells (hpDC), demonstrating that hpDC are susceptible to infection with the C#1 strain (attenuated) and even more susceptible to infection with the P (virulent) JUNV strain. However, hpDC elicited different responses in terms of viability, activation, maturation, and cytokine expression after infection with both JUNV strains.